PENGARUH METODE DEMONSTRASI TERHADAP HASIL BELAJARSENI RUPA SISWA KELAS XI SMA N 15 PADANG - AGUNG SAPUTRA, Dr.Ramalis Hakim, M.Pd. Drs. Abd. Hafiz,M.Pd (Universitas Negeri Padang, 2015)
The research is intendend to describe the differences of learning outcomesof students who are taught by using demonstration learning methods than those who are taught by using conventional in class XI SMA N 15 Padang. The data are taken from eleven grade student’s score. Data were analyzed by using a quasiexperimental research methodsthe technique of sampling of this research is purposive sampling. Results of experimental studies using the method of demonstration classes have an average higher than the control class using conventional methods. Based on t-test calculations obtained t = 5434 and table = 2,037 on the level of alpha = 0.05. it Show that are significant differences between the two classes in the second semester of the academic year 2014/2015.Kata Kunci: Metode Demonstrasi, Hasil Belajar, Seni Rupa